(untitled) (Journal of Mathematical Study, 2021)
We are concerned with super-Liouville equations on S^2, which have variational structure with a strongly-indefinite functional. We prove the existence of nontrivial solutions by combining the use of Nehari manifolds, balancing conditions and bifurcation theory.